Синтез многорежимных гидропневмоагрегатов - Вурье, Б. А.; Гордюхин, А. А. (НТУ "ХПИ", 2014)
Розглянуто етапи автоматизованого проектування раціональних схем автоматичних манiпуляторiв. Показана можливість синтезу багаторежимних схем гiдропневмоагрегатiв.

Stages of the automated designing of rational schemes of automatic manipulators are considered examined. The opportunity of synthesis of multimode schemes of hydropneu-mounits is shown.
Synthesis of multimode hydropneumounits
Keywords: пневмоагрегаты; автоматические манипуляторы; пневматические цилиндры; система управления